An e-commerce trust model based on expanded subjective logic. (2016) - Tian, Junfeng; Jiao, Hongqiang; Wang, Baomin; Chen, Chao
In current e-commerce, the trust relationship is difficult to establish and the computing trust value is imprecise. This paper proposes an e-commerce trust model based on expanded subjective logic. The model improves the evidence mapping operator, discounting operator and fusion operator in Jøsang's subjective logic. Through the introduction of trust wish value to new sellers, the unfairness of the current reputation mechanism is adjusted. The social network recommendation and the e-commerce trust model are combined, which makes the trust evaluation result more accurate. The trust path search algorithm is designed. It not only solves the issue about 'mass hysteria', but it also reduces the computation complexity. Finally, through the simulation experiment, the rationality and effectiveness of the model are verified.